Hubungan Komunikasi Interpersonal Mahasiswa Dengan Dosen Dan Antar Mahasiswa Dengan Motivasi Belajar - Prasetyo Catur Utomo; Ari Probandari (Poltekkes Kemenkes Surakarta, 2016)
Abstract : Interpersonal Communication, Learning Motivation. Interpersonal communication between students and lecturers and among students suspected to be a factor that will contribute to increase learning motivation . The purpose of this study, to measure the relationship of interpersonal communication between students and lecturer and among students with learning motivation at Prosthetic Orthotic Department of Health Polytechnic Surakarta. This study was descriptive analytic research with cross sectional approach. The population of this study were all students of Prosthetic Orthotic Department of Health Polytechnic Surakarta. 234 students. The sample were 150 students. The technique to choose the sample used simple random sampling. The technique to collect data used interpersonal communication questionnaires and learning motivation questionnaire. Data were analyzed using multiple linear regression analysis. There is statistically positive and significant correlation between interpersonal communication between students and lecturers and among students with learning motivation (r = 0.510). The impact amount of interpersonal communication between students and lecturers and among students with learning motivation is 26 % (r2 = 0.260). Interpersonal communication between students and lecturers and among students has correlation with learning motivation.